The Effects of Cultural Knowledge and Exposure on Speech and Language Assessments - Hemmerich, Abby; Lor, Yer (My University, 2017)
The purpose of this study was to examine the influence of culture on play-based interactions between a child and clinician. We hypothesize that a "cultural match" of a child and clinician will result in a more robust performance on speech and language assessment measures than situations of a "cultural mismatch."
Color poster with text, tables, and photos.
Keywords: Native American children; Speech-language pathologists; Bilingualism; African American children; White children; Posters; Hmong children; Culture; Play; Systematic Analysis of Language Transcripts (SALT)